Investigation and analysis on child rescue system from open bore well. Issue 2 (August 2020) - Karthik, S; Mohankumar, D K; Chandramohan, K; Udaiyakumar, K C
Abstract: In recent days, there are a lot of cases related to a child stuck in an open bore well. The actual methods involved in rescue are pulling the child using a rope with different knots or digging a parallel line beside the open bore using machines to the depth at which the child is stuck, the child is then pulled from the depth. But at deeper bore wells, these methods fail. This paper deals with a design to save a child who is stuck in manhole or open bore-well. Using this design the child can be easily rescued from the open bore wells, as this design includes hydraulic arm to hold the child with grips which won't slip due to sweat or wet condition of the bore well, the locking mechanism to hold the rescue system in one place inside the pit once it reaches the depth at which the child is stuck. A live streaming video surveillance for monitoring the child motion, oxygen supply channel for the child and a communication system to have contact.